IMPLEMENTASI HYPOTHETICAL LEARNING TRAJECTORY TERHADAP SOAL KONSTEKTUAL MATEMATIKA GARIS DAN SUDUT PADA SISWA KELAS VIII - Nurul Aien; Reni Gustia; Reri Seprina Anggraini (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This research aims to determine students' understanding of contextual questions on lines and angles and as a reference for mathematics teachers to improve students' understanding of contextual questions. In this research, researchers used descriptive qualitative methods. The data source in this research is class VIII students at SMPN 11 Sungai Penuh. The data collection technique in this research is by observing and documenting. Students can solve mathematical problems regarding lines and angles, but some students do not understand lines and angles because students are not given explanations or material that is contextual, as a result, students have difficulty describing contextual problems, so we as teachers must accompany students in the learning is especially for students who don't yet understand the contextual material of lines and angles.